Impact of Active Learning Strategies on Future Physics Teachers Disciplinary Knowledge in a Didactic Course [Impacto de Estrategias de Aprendizaje Activo Sobre el Conocimiento Disciplinar de Futuros Profesores de Física, en Un Curso de Didáctica] - Hernandez-Silva, C; Tecpan-Flores, S (Pontificia Universidad Catolica de Chile, 2018)
This article presents characteristics and results of a methodological intervention implemented in classes of a didactic course for initial training of physics teachers in a Chilean public university. The intervention consisted of teaching pre-service teachers about active learning strategies which they then used to design and conduct physics classes to their classmates. In order to measure the impact of the intervention on the level of disciplinary knowledge of future teachers, the Force Conceptual Inventory (FCI) was employed in pre and post instruction modality. The results show a normalized gain of 0.40 at the end of the intervention, suggesting that future physics teachers improved their level of conceptual understanding of disciplinary content after having learned and applied active learning strategies to teach peers. Implications for teacher training and study limitations are discussed by the authors. © 2018 PEL